2020
DOI: 10.3390/jcm9113678
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Shifts Induced by Physical Therapy in Lower Limb Lymphedema Patients

Abstract: Complete decongestive therapy (CDT), a physical therapy including manual lymphatic drainage (MLD) and compression bandaging, is aimed at mobilizing fluid and reducing limb volume in lymphedema patients. Details of fluid shifts occurring in response to CDT are currently not well studied. Therefore, we investigated fluid shifts before, during and after CDT. Thirteen patients (3 males and 10 females, aged 57 ± 8.0 years, 167.2 ± 8.3 cm height, 91.0 ± 23.4 kg weight) diagnosed with stage II leg lymphedema particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…Changes in plasma volume, especially central hypervolemia, are associated with changes in plasma protein (total protein, albumin, and albumin/globulin ratio), oncotic pressure, electrolyte concentrations (sodium, chloride, and potassium), osmolality, volume regulating hormones, and blood pressure. We observed that fluid shifts occur due to physical therapy and manual lymphatic drainage [ 139 ]. Manual lymphatic drainage affects the limbs and whole-body fluid composition.…”
Section: Complete Decongestive Therapymentioning
confidence: 99%
“…Changes in plasma volume, especially central hypervolemia, are associated with changes in plasma protein (total protein, albumin, and albumin/globulin ratio), oncotic pressure, electrolyte concentrations (sodium, chloride, and potassium), osmolality, volume regulating hormones, and blood pressure. We observed that fluid shifts occur due to physical therapy and manual lymphatic drainage [ 139 ]. Manual lymphatic drainage affects the limbs and whole-body fluid composition.…”
Section: Complete Decongestive Therapymentioning
confidence: 99%
“…An optimal and functioning lymphatic transport system is necessary to transport lipids absorbed in the gut, immune cells and to maintain fluid and macromolecular homeostasis [ 1 , 2 ]. Therefore, the lymphatic system is involved in several physiological processes, which has been reviewed elsewhere [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The lymphatic system is involved in the transport of fluid from tissue interstitial spaces. The lymphatic vessels move fluids and different compounds (such as immune cells, macromolecules and lipids) from the interstitium to larger veins [ 1 ]. Therefore, lymphatic transport is a fundamental component of the processes such as lipid absorption, management of body fluids, immune function and macromolecular homeostasis [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This fluid accumulation can reach up to 5-15 L [12]. Complete decongestive therapy (CDT) is a noninvasive, multicomponent physical treatment over three weeks that is usually applied to reduce swelling [13]. The physical treatment consists primarily of manual lymphatic drainage (MLD) and compression, as well as bandaging of the swollen body part, along with additional aerobic movements that provide leverage over the swelling.…”
Section: Introductionmentioning
confidence: 99%
“…In lymphedema patients, cardio-postural control might be affected due to different fluid volumes in the lower limbs, pre-and post-therapy, as well as due to plasma volume changes during physical therapy [10,13,15,16]. However, to our knowledge, there is no previous study focusing on investigating orthostatic intolerance during lymphedema therapy.…”
Section: Introductionmentioning
confidence: 99%